A Qualitative Approach to Assaying Customer Orientation and Market Dynamism of SMEs in Nigeria - Agumadu Mercy Adeola; Moses Chinonye Love; Adeniji Anthonia Adenike; Salau Odunayo Paul; Adeoye Funmilade (Communications of International Proceedings, 2020)
Entrepreneurs have to compete to survive in the ever-changing business environment especially during this Covid-19 Pandemic. Hence, there is an urgent need to find out solutions and survival strategy that can help cushion the effect of this crisis so that the SMEs can have a soft-landing at best. The study thus seek to find the influence of customer orientation on market dynamism. The study employed the qualitative approach where 12 top executives of registered four indigenous SMEs associations in Nigeria were interviewed. The study found out that customer orientation has a significant effect on market dynamism and the study recommended that entrepreneurs should involve in thorough analysis and modelling of the business during any market change and the customers satisfaction should be taken as top priority.
Keywords: Market; Customer; Pandemic; Dynamism; Entrepreneurs